Pericytes: multitasking cells in the regeneration of injured, diseased, and aged skeletal muscle - Birbrair, Alexander; Zhang, Tan; Wang, Zhong-Min; Messi, Maria L.; Mintz, Akiva; Delbono, Osvaldo (Frontiers in Aging Neuroscience, 2014)
Pericytes are perivascular cells that envelop and make intimate connections with adjacent capillary endothelial cells. Recent studies show that they may have a profound impact in skeletal muscle regeneration, innervation, vessel formation, fibrosis, fat accumulation, and ectopic bone formation throughout life. In this review, we summarize and evaluate recent advances in our understanding of pericytes’ influence on adult skeletal muscle pathophysiology. We also discuss how further elucidating their biology may offer new approaches to the treatment of conditions characterized by muscle wasting.